2015
DOI: 10.1001/jamasurg.2015.0287
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities Associated With Initial Hemodialysis Access

Abstract: Black patients and Hispanic patients tend to initiate hemodialysis with an AVF less frequently than white patients despite being younger and having fewer comorbidities. These disparities persisted independent of factors that drive health access for fistula placement, such as medical insurance status and nephrology care. The sociocultural underpinnings of these disparities deserve investigation and redress to maximize the benefits of initiating hemodialysis via fistula in patients with end-stage renal disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 31 publications
(19 reference statements)
5
56
0
Order By: Relevance
“…Zarkowsky et al [13] reported that white patients had a 22% greater chance than did black patients of initiating hemodialysis with an AV fistula versus combined groups of AV graft and catheter. Our study modeled the use of permanent AV access (AV fistula or AV graft) compared to catheter or others; and found that blacks had 8% higher adjusted odds of using permanent access compared to whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zarkowsky et al [13] reported that white patients had a 22% greater chance than did black patients of initiating hemodialysis with an AV fistula versus combined groups of AV graft and catheter. Our study modeled the use of permanent AV access (AV fistula or AV graft) compared to catheter or others; and found that blacks had 8% higher adjusted odds of using permanent access compared to whites.…”
Section: Discussionmentioning
confidence: 99%
“…Women are shown to have lower probability of receiving AV fistula than men [12]. Zarkowsky et al [13] reported that Hispanic or black patients tend to use AV fistula less frequently than white patients to initiate hemodialysis; but did not consider AV graft as one of the parameters of successful AV access [13]. Prior studies stratified by race did not look at gender differences among them, or took into account Asian and Native American patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent national analysis of all patients with ESRD in the USRDS revealed the lower rates of initiating dialysis with an arteriovenous fistula for black and Hispanic patients than whites, but the analysis did not assess contextual factors jointly with the patient factors (35). The few studies that examined contextual factors found some particular aspects of residential areas associated with the lower likelihood of patients having received pre-ESRD care, including residential areas with larger proportions of black residents (23), counties with greater poverty (25), large metropolitan or rural counties (24), or states with more stringent Medicaid coverage (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Arce et al [29] demonstrated that Hispanics were significantly less likely to use an arteriovenous access for the first outpatient HD treatment compared with non-Hispanics (prevalence ratio 0.94). More recently, in a USRDS cohort of 396,075 patients initiating dialysis between 2006 and 2010, Zarkowsky et al [30] reported that white patients were significantly more likely to initiate HD with an AVF than AA (aOR 1.22) and Hispanic (aOR 1.32) patients. Key differences between that study and the current study are that we assessed measures of poverty in our model and ours is a larger cohort.…”
Section: Discussionmentioning
confidence: 99%